Theoretical ab initio study of the electric field effects on the structure and stability of G:C base pair - Al-Anber, Mohanned J. (Array, 2008)
Summary: The effect of applied external electric field on DNA occurs mostly at high field intensity. The results of a theoretical ab initio study of effects of applied electric field on G:C base pair components are reported. The geometries of the local minima were optimized without the symmetry restrictions by the gradient procedure at density-functional level of the theory and were verified by calculations of the second derivative of energy. The standard CEP-31G basis set was used. The geometrical parameters, relative stability and interaction energies are reported. The electric field mutation could be classified as a multi-point mutation